CARD9 as a potential target in cardiovascular disease - Peterson MR; Haller SE; Ren J; Nair S; He G (Dove Medical Press, 2016)
Matthew R Peterson, Samantha E Haller, Jun Ren, Sreejayan Nair, Guanglong He School of Pharmacy, University of Wyoming, College of Health Sciences, Laramie, WY, USA Abstract: Systemic inflammation and localized macrophage infiltration have been implicated in cardiovascular pathologies, including coronary artery disease, carotid atherosclerosis, heart failure, obesity-associated heart dysfunction, and cardiac fibrosis. Inflammation induces macrophage infiltration and activation and release of cytokines and chemokines, causing tissue dysfunction by instigating a positive feedback loop that further propagates inflammation. Cytosolic adaptor caspase recruitment domain family, member 9 (CARD9) is a protein expressed primarily by dendritic cells, neutrophils, and macrophages, in which it mediates cytokine secretion. The purpose of this review is to highlight the role of CARD9 as a potential target in inflammation-related cardiovascular pathologies. Keywords: inflammation, heart failure, pressure-overload, hypertension